IN THE WORLD OF LANGUAGES - Chugaeva, T.N.; Shpak, N.E.; Nazmutdinova, S.S. (Perm Federal Research Centre Journal, 2018)
The article looks into the publication of the new book entitled “Terra Linguaе: In the world of languages”. The scientific project is introducing to the reader the language as a unique phenomenon of culture, collective philosophy expressed by linguistic forms. The book came out in February 2018 and since then it has been presented in Perm, Saint Petersburg and Grozny (Chechen Republic). On March 15th, 2018 the Perm Federal Research Center UB RAS initiated and held its presentation at Perm State Regional Library named after A. M. Gorky.